The effects of broiler chickens diet containing Fermented Pineapple Peel Meal (FPPM) on the performance and Income Over Feed and Chicken Cost (IOFCC) - Apedro, Henggi; Khunhareng, Sajee; Phasuk, Yupin (วารสารแก่นเกษตร, 2023)
The research herein aimed to compare the supplementation of fermented pineapple peel meal (FPPM) at different levels in broiler diets on the performance and income over feed and chicken cost (IOFCC). A total of 400 male broiler finishers with 1-day-old chick (Cobb-500 from 38-week-old breeders) were used in this experiment, divided into four treatment groups, and kept until the birds' final body weight reached 1.5 kg (market size). The FPPM was then incorporated into the experimental diets treatment at; T1 = 100% Commercial feed + 0% FPPM; T2 = 95% Commercial feed + 5% FPPM; T3 = 90% Commercial feed + 10% FPPM; T4 = 85% Commercial feed + 15% FPPM. The study was conducted in a completely random design (CRD), and the treatments were replicated four times each. Parameters were evaluated: feed intake, initial weight, final weight, average daily gain (ADG), body weight gain (BWG), feed conversion ratio (FCR), and IOFCC. Data were analyzed by analysis of variance (ANOVA), and duncan's multiple range tested was used for mean comparisons. The results showed no significant differences (P>0.05) in the initial weight and ADG starter; Offered FPPM in the chicken diet significantly (P<0.05) increased feed intake; and showed highly significant differences (P<0.01) in the final weight, ADG finisher, BWG, and FCR. Therefore, it can be concluded that FPPM might be mixed up to 5% without any significant adverse effects on growth performance and improved the IOFCC. However, 15% of FPPM showed the highest IOFCC in any sales type compared to the control diet treatment.